Variability in Tidal Volume Affects Lung and Cardiovascular Function Differentially in a Rat Model of Experimental Emphysema - Wierzchon, Caio G. R. S.; Padilha, Gisele; Rocha, Nazareth N.; Huhle, Robert; Coelho, Mariana S.; Santos, Cintia L.; Santos, Raquel S.; Samary, Cynthia S.; Silvino, Fernanda R. G.; Pelosi, Paolo; Gama de Abreu, Marcelo; Rocco, Patricia R. M.; et al. (Frontiers in Physiology, 2017)
In experimental elastase-induced emphysema, mechanical ventilation with variable tidal volumes (VT) set to 30% coefficient of variation (CV) may result in more homogenous ventilation distribution, but might also impair right heart function. We hypothesized that a different CV setting could improve both lung and cardiovascular function. Therefore, we investigated the effects of different levels of VT variability on cardiorespiratory function, lung histology, and gene expression of biomarkers associated with inflammation, fibrogenesis, epithelial cell damage, and mechanical cell stress in this emphysema model. Wistar rats (n=35) received repeated intratracheal instillation of porcine pancreatic elastase to induce emphysema. Seven animals were not ventilated and served as controls (NV). Twenty-eight animals were anesthetized and assigned to mechanical ventilation with a VT CV of 0% (BASELINE). After data collection, animals (n=7/group) were randomly allocated to VT CVs of 0% (VV0); 15% (VV15); 22.5% (VV22.5); or 30% (VV30). In all groups, mean VT was 6 mL/kg and positive end-expiratory pressure was 3cmH2O. Respiratory system mechanics and cardiac function (by echocardiography) were assessed continuously for 2 hours (END). Lung histology and molecular biology were measured post-mortem. VV22.5 and VV30 decreased respiratory system elastance, while VV15 had no effect. VV0, VV15, and VV22.5, but not VV30, increased pulmonary acceleration time to pulmonary ejection time ratio. VV22.5 decreased the central moment of the mean linear intercept (D2 of Lm) while increasing the homogeneity index (1/β) compared to NV (77±8µm vs. 152±45µm; 0.85±0.06 vs. 0.66±0.13, p<0.05 for both). Compared to NV, VV30 was associated with higher interleukin-6 expression. Cytokine-induced neutrophil chemoattractant-1 expression was higher in all groups, except VV22.5, compared to NV. IL-1β expression was lower in VV22.5 and VV30 compared to VV0. IL-10 expression was higher in VV22.5 than NV. Club cell protein 16 expression was higher in VV22.5 than VV0. SP-D expression was higher in VV30 than NV, while SP-C was higher in VV30 and VV22.5 than VV0. In conclusion, VV22.5 improved respiratory system elastance and homogeneity of airspace enlargement, mitigated inflammation and epithelial cell damage, while avoiding impairment of right cardiac function in experimental elastase-induced emphysema.